(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The root mealybug Rhizoecus hibisci Kawai & Takagi is regularly intercepted in The Netherlands on bonsai-trees originating from China. The main host of this quarantine organism is Se rissa sp. but it has been found on other plant species as well. Observations on a single specimen on Serissa plants in a container showed that one generation at 21°C lasts two months starting from the beginning of the first stage whereas on Nerium at the same temperature its life cycle is much longer. Males may be present but single female specimens can reproduce parthenogenetically. Examination of slide mounted specimens of mixed stage populations showed the existence of three larva! instars. The number of dorsal abdominal ducts, the number of trilocular pores and the number of setae on the posterior margin of the posterior ostiole, appeared to be some of the most important discriminating characters.